Cross‐Shore Structure of Tidally Driven Alongshore Flow Over Rough Bathymetry. Issue 8 (31st July 2020) - Amador, A.; Arzeno, I. B.; Giddings, S. N.; Merrifield, M. A.; Pawlak, G.
Abstract: A tidally driven alongshore flow on the western coast of O'ahu Hawai'i is examined using velocity measurements from an autonomous underwater vehicle (AUV) along with time series observations of the alongshore pressure gradient. Depth‐averaged velocities over the forereef shelf are reconstructed from AUV‐based velocity observations as a function of cross‐shore distance assuming a sinusoidal tidal periodicity. Ensemble phase averages of the alongshore pressure gradient and velocities from multiple AUV surveys reveal characteristics akin to an oscillatory boundary layer, with the nearshore flow leading the offshore flow in phase and with a corresponding velocity attenuation at shallower depths. Analysis of the depth‐averaged alongshore momentum equation indicates that the cross‐shore structure and evolution of the tidal boundary layer is well described by a balance between the local acceleration, the barotropic pressure gradient, and bottom drag. This primary balance allows estimation of the drag coefficient as a function of cross‐shore distance over depths spanning from 24 to 6 m. Results indicate that drag coefficients range from 0.004 to 0.010 [±0.002] over a 600 m cross‐shore forereef section. These estimates are in good agreement with previous results obtained at the 12 m isobath using fixed observations and compare favorably with roughness estimates from LIDAR and AUV‐based mapping. Roughness data suggest that larger scales, with wavelengths of O (10 m), play a more significant role than smaller meter‐scale roughness in determining the drag on the tidal flow. Plain Language Summary: Flow in the inner shelf region outside of the surf zone regulates cross‐shelf transport of heat, mass, and momentum, affecting coastal distributions of larvae and nutrients as well as pollutants. This transport is strongly affected by the structure and variability in the predominantly alongshore flow and by turbulence driven by flow over the rough seabed. This study examines the cross‐shore structure of the alongshore tidally driven flow for a coral forereef environment on the western coast of O'ahu, Hawai'i, using velocity measurements obtained using an autonomous underwater vehicle (AUV) along with measurements of pressure and velocity from fixed, bottom‐mounted instruments. The tidal periodicity of the flow allows a reconstruction of the spatial flow structure over an average tidal cycle which highlights strong frictional effects close to shore that weaken with distance from shore. The observed alongshore flow structure is well described by a simple momentum balance between pressure force, acceleration, and friction which yields estimates of the bottom drag coefficient as a function of cross‐shore distance. Comparisons between cross‐shore patterns in drag and bottom roughness indicate that the flow is best correlated with longer wavelength roughness (>20 m). Key Points: Observations of a tidally driven alongshore flow reveal characteristics akin to an oscillatory boundary layer The cross‐shore flow structure is well described by a 1‐D balance between local acceleration, barotropic pressure gradient, and bottom drag Drag coefficient estimates and roughness data suggest that features with wavelengths of O (10 m) play a dominant role in determining bottom drag